Management of the risk of coronary and peripheral revascularization within 3 years after coronary angiography in patients with coronary artery disease - D. К. Vasiliev; N. L. Bogdanova; N. G. Gumanova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To develop an approach to reduce the frequency of urgent coronary and peripheral revascularization by influencing modifiable risk factors.Material and methods. A cohort of patients with coronary artery disease (n=218; 63±10,9 years, 54% men) who underwent coronary angiography (CAG), including stenting. A number of routine anthropometric and biochemical parameters were analyzed in all patients. Statistical analysis was performed using Statistica version 8.0 and SPSS IBM statistics 23 software using ROC analysis, binomial logistic regression, 2´2 contingency tables and Pearson c2 for hypothesis testing.Results. A combination of noninvasive parameters associated with the maximum relative risk (RR) of coronary and peripheral artery revascularization over the 3 years after CAG was identified (RR=15 (95% confidence interval (CI): 5,96-36,5, p=0,001), compared with other possible combinations of the studied parameters. This combination included waist circumference with a limit of 89 cm, smoking status, and four following biochemical markers: C-reactive protein with a limit of 3,4 mg/l, glucose with a limit of 7,6 mmol/l, insulin with a limit of 10 μU/ml, and low-density lipoprotein cholesterol with a limit of 2,9 mmol/l.Conclusion. A scale-table of the relative risk (RR) of coronary and peripheral revascularization over the 3 years after elective diagnostic CAG. The scale-table demonstrates the possibility of managing the risk of coronary and peripheral revascularization after CAG and motivating the patient to modify risk factors.